Online-based English Listening Skill Learning Model - Atmowardoyo, Haryanto; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2022)
This article is part of a research entitled "Online-based Student English Learning Models in Facing Curriculum Changes in the New Normal Era". This research was conducted to see and identify online-based listening learning models for students. The research method used is a descriptive qualitative method using a questionnaire and the final assignment of the Project course (Lesson Plan and Instruction). The number of samples used was 52 students who took the Project course (Lesson Plan and Instruction). From the 52 students, 6 students chose to teach the listening skill. Data analysis includes observation, open coding, and axial coding. The results reveal that the media used by students in learning listening skills is divided into online and offline media each 50% (3 people. Applications used by students in learning listening skill are divided into the use of British Council Web (16.67%), YouTube (16.67%), Google Meet (16.67%) and offline learning/Face-to-Face (50%). The learning methods that students apply in learning listening are Audio-Lingual Method (66.67%), Scientific Approach Techniques (16.67%), and Community Language Learning (16.67%). The topics presented included: Listening, Procedure Text, Songs, Job Application Letter, and Listening to a short cut of film.